(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The turnout of low skilled technical graduates which have increased unemployment rate and skill shortages in the technical education field and building construction sector, have resulted to doubts, if the technical teachers possess sufficient skills in Building Drawing. This situation necessitated the determination of the competency improvement needs of Building Drawing teachers for effective performance, in Colleges of Education, in South-South and South-East Nigeria. The purpose of the study was to determine the competency improvement needs of Building Drawing teachers for effective performance in; the use of drafting tools, basic design process and computer aided design (CAD). Two research questions guided the study. Two null hypotheses were also tested at 0.05 level of significance. A survey research design was adopted for the study. The population for the study was 104 Building Drawing teachers from the Colleges of Education offering technical education programmes. The entire population was used for the study without sampling. A 24 item questionnaire structured on a five point rating scale was the instrument used for data collection. One hundred and four copies of the questionnaire were administered on the respondents with 88 percent returned rate. The instrument was validated by three experts. Cronbach alpha reliability co-efficient method was used to test the reliability of the instrument. The reliability co-efficient obtained for the two clusters were 0.81 and 0.64 with 0.73 overall reliability co-efficient obtained. Data collected were analysed using mean, standard deviation and t-test statistics. Findings revealed that building drawing teachers in South-South and South-East Nigeria need improvement in most skill areas. Urgent attention is required in Computer Aided Design (CAD) knowledge. The tests of hypotheses revealed no significant differences between the mean ratings of male and female teachers in the use of drafting tools and materials, while significant difference existed in CAD usage. Based on the findings of the study, it was recommended among others that functional drawing studios with modern facilities such as CAD work stations be made available for teaching and learning of building drawing in Colleges of Education. Training programmes to build the teachers’ competencies in all aspects of building drawing should be prioritized in Colleges of Education in both regions.